Kajian Variasi Pengolahan Teh Daun Sirsak, Sifat Fisik, Organoleptik Dan Kadar Vitamin E - Saila Maharani; Idi Setyobroto; Joko Susilo (POLTEKKES KEMENKES YOGYAKARTA, 2017)
Soursop leaf tea is a beverage product that has a high antioxidant consistency, so that many benefits are obtained whentaking it. It can be a healthy alternative beverage by knowing the best processing method and the content of soursop leaves.Soursop leaf contains vitamin E of 12.05 g / 100gr, it also has other steroid / terpenoids, flavonoids, coumarin, alkaloids andtannins. Flafonoid has functions as antioxidant for cancer, anti-microbial, anti-virus regulator of photosynthesis and plantgrowth regulator. The highest nutrient the soursop leaf is vitamin E so it is beneficial for health. The purpose of this study is todetermine the best processing method and know the content of soursop leaf tea processing and this study aims to determinethe different variation in processing soursop leaf tea reviewed from the physical characteristic, the organoleptic characteristicand vitamin E of the product.This type of research was Random Simple (US) using two treatments, each treatment was done with twice repetition andthree times of the experiment so it had 18x experimental unit. The data of the physical characteristic were analyzeddescriptively and the organoleptic characteristic data were analyzed with the Kruskal-Wallis test while the data of vitamin Elevel were analyzed descriptively. The results of the physical characteristics showed that tea has dark brown color, distinctivearoma of soursop leaves and a very bitter taste. The organoleptic characteristic resulted the most preferred color was frombrewed soursop leaf tea, the best taste was from boiled soursop leaf tea and the most preferred aroma was from boilingprocess. The highest level of vitamin E was tea powder that had not been processed into drinks. The conclusion from thisstudy is the best variation of soursop leaf tea processing on the physical properties (color, aroma, flavor) organolepticproperties (color, aroma, flavor) and vitamin E is the boiling process.